Classificatory struggles: class, culture and inequality in neoliberal times. Issue 2 (May 2015) - Tyler, Imogen
Abstract The problem that the concept of 'class' describes is inequality. The transition from industrial to financial capitalism (neoliberalism) in Europe has effected 'deepening inequalities of income, health and life chances within and between countries, on a scale not seen since before the second world War' (Hall et al., 2014: 9). In this context, class is an essential point of orientation for sociology if it is to grasp the problem of inequality today. Tracing a route through Pierre Bourdieu's relational understanding of class, Beverley Skeggs' understanding of class as struggles (over value), and Wendy Brown's argument that neoliberalism is characterized by the culturalization of political struggles, this article animates forms of class‐analysis, with which we might better apprehend the forms of class exploitation that distinguish post‐industrial societies. Taking a cue from Jacques Rancière, the central argument is that the sociology of class should be grounded not in the assumption and valorization of class identities but in an understanding of class as struggles against classification. In this way, sociology can contribute to the development of alternative social and political imaginaries to the biopolitics of disposability symptomatic of neoliberal governmentality.